Understanding the Danger of Word of Mouth in Creating New Smokers and the Factors that Influence It and Its Prevention - Muhammad Johan Widikusyanto; Widya Nur Bhakti Pertiwi; Arum Wahyuni Purbohastuti; Farah Putri Wenang Lusianingrum (Tirtayasa Ekonomika, 2025)
The number of active smokers in Indonesia is rising, especially among teenagers, leading to over 200,000 deaths annually. This concerning trend calls for urgent research. This study examines how word of mouth influences new smokers and explores the effects of products, promotions, and reference groups on smoking attitudes and behaviors. It also investigates their indirect impact on word of mouth. A survey of 593 active smokers was conducted using structured questionnaires, with data analyzed through Structural Equation Modeling (SEM). Results show that products, promotions, and reference groups directly influence smoking attitudes and behaviors and indirectly affect word of mouth. However, the link between smoking attitudes and smoking behavior was not supported. Among the factors, promotions had the strongest impact. These insights suggest that demarketing strategies should be developed to curb smoking behavior effectively.